2016
DOI: 10.5539/ibr.v9n10p201
|View full text |Cite
|
Sign up to set email alerts
|

Does Shopping Preparation influence Consumer Buying Decisions?

Abstract: Changes in consumers" environment, specifically the economic crisis and the growing penetration of digital technologies, have produced significant changes in shopping habits, designed to gradually reduced the effectiveness of in-store marketing levers in influencing shopping behaviour. On one hand, due to the global economic downturn and the associated diminished disposable income, more shoppers are now searching more information before entering a store and evaluating more alternatives before to decide where a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…In a retail environment, mobile devices and new applications for smartphones allow shoppers to scan product barcodes, compare prices across retailers or obtain digital coupons to be redeemed in store. The usage of technologies in pre-shopping phase could help shoppers to make better decision and being less influenced by the environment while expending less effort inside the store (Bellini et al, 2016). Therefore, digital tools may have positive effects on both the quality and the efficiency of purchase decisions inside the store.…”
Section: Decision-making Process and Mobile Usementioning
confidence: 99%
See 2 more Smart Citations
“…In a retail environment, mobile devices and new applications for smartphones allow shoppers to scan product barcodes, compare prices across retailers or obtain digital coupons to be redeemed in store. The usage of technologies in pre-shopping phase could help shoppers to make better decision and being less influenced by the environment while expending less effort inside the store (Bellini et al, 2016). Therefore, digital tools may have positive effects on both the quality and the efficiency of purchase decisions inside the store.…”
Section: Decision-making Process and Mobile Usementioning
confidence: 99%
“…The analysis of the factors influencing the consumer's decision making process inside the store has always interested researchers (Kollat & Willet, 1967;Iyer & Ahlawat, 1987;Iyer, 1989;Donovan, Rossiter, Marcoolyn & Nesdale, 1994;Inman, Winer & Ferraro, 2009;Mohan, Sivakumaran & Sharma, 2013;Shankar, 2014;Bellini et al, 2016). Nevertheless, the impact and the role of mobile technologies, such as smartphones and other mobile devices, is a subject still little explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying the list of grocery items including food to purchase before going to the grocery store can be a strategy to maintain good health (15). The consumers adopted the planning stage as a self-control strategy to avoid impulsive purchases at the grocery store (16).…”
Section: Background and Related Studiesmentioning
confidence: 99%
“…A grocery list serves as a tool to keep track of the items to be purchased in physical stores, consequently has been a subject for scientific studies (18). Studies have shown that the existence of a written grocery list increases the probability of purchasing the planned grocery items (16).…”
Section: Background and Related Studiesmentioning
confidence: 99%